2011
DOI: 10.1124/jpet.110.177790
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Antivascular Endothelial Growth Factor Strategies in Experimental Dopamine-Resistant Prolactinomas

Abstract: Prolactin-secreting adenomas are the most frequent type among pituitary tumors, and pharmacological therapy with dopamine agonists remains the mainstay of treatment. But some adenomas are resistant, and a decrease in the number or function of dopamine D2 receptors (D2Rs) has been described in these cases. D2R knockout [Drd2(Ϫ/Ϫ)] mice have chronic hyperprolactinemia and pituitary hyperplasia and provide an experimental model for dopamine agonist-resistant prolactinomas. We described previously that disruption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…In support of the recent report by Luque et al (2011) that demonstrated inhibitory effects of anti-VEGF strategies in experimental dopamine-resistant prolactinomas, these findings suggest an important role of VEGF signaling in pituitary tumor growth. Pituitary tumors may have a lower microvessel density compared with the highly vascularized normal pituitary gland, but hypoxic conditions within the tumor may still activate the RSUME-HIF1a-VEGF pathway leading to increased vascularization or more ordered microvascular geometry in order to sustain tumor growth.…”
Section: Pituitary Tumor Hif1a-vegf Pathwaysupporting
confidence: 75%
“…In support of the recent report by Luque et al (2011) that demonstrated inhibitory effects of anti-VEGF strategies in experimental dopamine-resistant prolactinomas, these findings suggest an important role of VEGF signaling in pituitary tumor growth. Pituitary tumors may have a lower microvessel density compared with the highly vascularized normal pituitary gland, but hypoxic conditions within the tumor may still activate the RSUME-HIF1a-VEGF pathway leading to increased vascularization or more ordered microvascular geometry in order to sustain tumor growth.…”
Section: Pituitary Tumor Hif1a-vegf Pathwaysupporting
confidence: 75%
“…Indeed, it has been demonstrated that VEGF expression was associated with pituitary tumorigenesis [14] and somatostatin analogues (octreotide or pasireotide) inhibit NFPA cell viability by inhibiting VEGF secretion [15]. Moreover, recent studies demonstrated that the antiangiogenic approach using anti-VEGF antibody [16] or a small-molecule tyrosine kinase inhibitor (lapatinib) [17] targeting EGF receptors Erb1 and Erb2 was effective, in inhibiting in vivo the growth of dopamineresistant prolactinoma from dopamine receptor D2R mouse knockout [16] or in estrogen-induced Fischer344 rat prolactinomas [17]. More recently, Liu et al identified a pharmacologic CDK2/cycline E inhibitor, R-roscovitine, and demonstrated that R-roscovitine suppressed ACTH expression and induced ACTH tumor cell senescence using a transgenic fish model and AtT20 ACTH tumor cells injected in nude mice [18].…”
Section: Discussionmentioning
confidence: 98%
“…Disease processes which have been shown to increase vascularity include, in particular, endocrine glands illness [24,25], acromegaly [19], pituitary adenomas [26,27], autoimmune thyroid disease, goitre, neoplasms [18,22] and eye disorders -retinopathy occurring in premature infants [18,28], diabetic retinopathy [18,20,21,[29][30][31], uveitis and other ocular illnesses. Angiogenesis commonly occurs in inflammatory diseases [18-20, 22, 24-27].…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis is an important component of many physiological and pathological processes [16][17][18][19][20][21][22][23][24][25][26][27]. Disease processes which have been shown to increase vascularity include, in particular, endocrine glands illness [24,25], acromegaly [19], pituitary adenomas [26,27], autoimmune thyroid disease, goitre, neoplasms [18,22] and eye disorders -retinopathy occurring in premature infants [18,28], diabetic retinopathy [18,20,21,[29][30][31], uveitis and other ocular illnesses.…”
Section: Introductionmentioning
confidence: 99%